Composite solid electrolyte and preparation method thereof
By using a PEO-type copolymer containing crosslinkable functional groups and a ceramic compound in the composite solid electrolyte and performing a vapor-phase deposition active compound, the problem of low ionic conductivity of the composite solid electrolyte in the prior art is solved, and higher ionic conductivity and mechanical properties are achieved.
Patent Information
- Application Number
- CN202380062051.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-04
AI Technical Summary
Existing composite solid electrolytes have limitations in improving ionic conductivity, especially when using highly crystalline polymers such as PEO, the movement of lithium ions is limited.
By introducing a mixture of PEO-type copolymer containing crosslinkable functional groups into the composite solid electrolyte and a ceramic compound, and vapor-phase deposition of active compounds in the polymer, to form a three-dimensional network structure and improve the mobility of lithium ions.
While maintaining the inherent structural properties of the polymer, it is achieved to improve the mobility of the polymer chain and uniform dispersion of ceramic particles, thereby significantly improving the ionic conductivity and mechanical properties of the composite solid electrolyte.
Smart Images

Figure BDA0005285675800000031 
Figure BDA0005285675800000032 
Figure BDA0005285675800000033
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0132765, filed on October 14, 2022, and Korean Patent Application No. 10-2023-0136066, filed on October 12, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to a composite solid electrolyte and a preparation method thereof. Background Art
[0004] Lithium-ion batteries using liquid electrolytes have a structure where the negative and positive electrodes are bounded by a separator. Therefore, if the separator is damaged by deformation or external impact, it can cause a short circuit, resulting in hazards such as overheating or explosion. Therefore, the development of a solid electrolyte that ensures safety is a crucial issue in the field of lithium-ion secondary batteries.
[0005] The advantages of lithium secondary batteries using solid electrolytes include enhanced safety, improved reliability due to electrolyte leakage prevention, and the ability to manufacture thin batteries. Furthermore, lithium metal can be used as the negative electrode to increase energy density. Therefore, in addition to compact secondary batteries, these lithium secondary batteries using solid electrolytes are expected to be used in high-capacity secondary batteries for electric vehicles and are attracting attention as next-generation batteries.
[0006] Among solid electrolytes, polymer solid electrolytes may be composed of an ion-conductive polymer material and may be used in the form of a composite solid electrolyte in which such a polymer material is mixed with an inorganic material.
[0007] This conventional hybrid (composite) solid electrolyte is prepared by dispersing inorganic powders such as oxide ceramics in a polymer matrix. Its advantages are higher ignition and combustion stability compared to existing liquid electrolytes and higher ionic conductivity compared to polymer solid electrolytes, but its difficulty lies in meeting basic prerequisites, such as improving the dispersibility of oxide ceramic particles in the polymer matrix and optimizing the physical properties of the polymer matrix used. In particular, when a highly crystalline polymer such as polyethylene oxide (PEO) is used as a matrix, there is a problem of difficulty in preparing a composite solid electrolyte with improved ionic conductivity. In other words, due to the high crystallinity of the PEO polymer, the chain mobility of the polymer is suppressed, and the movement of lithium ions inside the polymer solid electrolyte is restricted. Therefore, there are limitations in improving the ionic conductivity of polymer solid electrolytes.
[0008] In order to overcome the limitations of conventional composite solid electrolytes, attempts have been made to change the structure of crystalline polymers or add separate plasticizers to the polymers to improve the mobility of polymer chains and enhance the ionic conductivity of the composite solid electrolytes. However, it is difficult to improve the ionic conductivity of the composite solid electrolytes by simply deforming the polymer structure and adding plasticizers.
[0009] Therefore, it is necessary to develop a technology that can improve the ionic conductivity of composite solid electrolytes by methods other than structural deformation of polymers and addition of plasticizers.
[0010] [Prior art literature]
[0011] [Patent Document]
[0012] (Patent Document 0001) Japanese Patent Application Laid-Open No. 1994-124713 Summary of the Invention
[0013] [Technical Issues]
[0014] An object of the present disclosure is to provide a composite solid electrolyte and a method for preparing the same, which can improve ion conductivity even when a very small amount of a polar compound (eg, a polar solvent compound) is added to the composite solid electrolyte in a non-liquid state.
[0015] Another object of the present disclosure is to provide an all-solid-state battery comprising the above-mentioned composite solid electrolyte, thereby exhibiting improved ionic conductivity, etc.
[0016] [Technical solution]
[0017] According to one embodiment of the present disclosure, a composite solid electrolyte is provided, comprising: a polymer comprising a PEO (polyethylene oxide)-type copolymer containing a cross-linkable functional group; a ceramic compound; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-links with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to a polymer chain.
[0018] In the composite solid electrolyte, the gaseous polar compound is dispersed between polymer chains forming a three-dimensional network structure, or may be adsorbed or bonded to the surface or interior of the polymer chains.
[0019] In addition, the composite solid electrolyte may further include a crosslinking agent. In this case, at least a portion of the crosslinkable functional groups may form crosslinked bonds with each other through the crosslinking agent.
[0020] In the composite solid electrolyte, the PEO-based copolymer may contain one or more, or two or more, crosslinkable functional groups. The crosslinkable functional group is bonded to the chain of the PEO-based copolymer by an alkylene linker or an alkylene oxide linker having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and may be a functional group selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
[0021] In addition, the composite solid electrolyte may further include a lithium salt, wherein the lithium salt may be contained in a state of at least partially dissociated cations and anions. The cations and / or anions may exist in a state bound to the polymer and may be mobile during charge / discharge of the battery.
[0022] In a specific embodiment, the PEO (polyethylene oxide)-based copolymer of the composite solid electrolyte may be a copolymer containing repeating units of the following chemical formulas 1 to 3:
[0023] [Chemical Formula 1]
[0024]
[0025] [Chemical Formula 2]
[0026]
[0027] [Chemical Formula 3]
[0028]
[0029] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding to the polymer chain one or more crosslinkable functional groups selected from the group consisting of hydroxyl, carboxyl, isocyanate, nitro, cyano, amine, amide, epoxy and allyl groups through an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein the alkylene linker having 0 carbon atoms represents a single bond), and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
[0030] On the other hand, in such a composite solid electrolyte, the content of the polar compound may be 0.1 wt % or more and less than 10 wt % based on the total weight of the composite solid electrolyte.
[0031] In addition, the polar compound may include at least one selected from the group consisting of carbonate compounds and sulfonyl compounds, and may be a polar compound derived from a carbonate solvent or a sulfonyl solvent and contained in a gaseous state. More specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.
[0032] In addition, the ceramic compound may include an oxide-based solid electrolyte selected from lithium metal oxide or lithium metal phosphorus oxide, more specifically, may include at least one oxide-based solid electrolyte selected from the group consisting of lithium lanthanum zirconium oxide (LLZO) compounds, lithium silicon titanium phosphate (LSTP) compounds, lithium lanthanum titanium oxide (LLTO) compounds, lithium aluminum titanium phosphate (LATP) compounds, lithium aluminum germanium phosphate (LAGP) compounds and lithium lanthanum zirconium titanium oxide (LLZTO) compounds.
[0033] On the other hand, according to another embodiment of the present disclosure, a method for preparing a composite solid electrolyte of the present invention is provided, the method comprising the following steps: (S1) mixing a PEO (polyethylene oxide)-type copolymer containing a cross-linkable functional group with a ceramic compound, and then subjecting the PEO-type copolymer contained in the mixture to a cross-linking reaction; and (S2) vapor-depositing a polar solvent on the mixture containing the polymer cross-linked in step (S1).
[0034] In this preparation method, the cross-linking reaction of step (S1) may be performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.
[0035] On the other hand, in the production method, the polar solvent may be a polar solvent corresponding to the polar compound of one embodiment.
[0036] Furthermore, in the preparation method, in step (S2), vapor of the polar solvent is deposited on the polymer so that the content of the polar solvent is 0.1 wt% or more and less than 10 wt% based on the total weight of the composite solid electrolyte.
[0037] According to yet another embodiment of the present disclosure, an all-solid-state battery is provided, comprising an electrolyte layer, wherein the electrolyte layer comprises the composite solid electrolyte according to one embodiment described above.
[0038] [Beneficial Effects]
[0039] The composite solid electrolyte of one embodiment of the present disclosure improves the mobility of the polymer chain while maintaining the inherent structural properties of the polymer and uniformly distributes the ceramic particles in the composite solid electrolyte without deforming or breaking the polymer chain, thereby improving the ionic conductivity of the composite solid electrolyte.
[0040] In addition, the composite solid electrolyte contains a very small amount of gaseous polar compounds, which can improve the ionic conductivity and mechanical properties of the composite solid electrolyte.
[0041] Furthermore, when a polar solvent is included in the composite solid electrolyte via vapor deposition, gelation is prevented, the relaxation time of the internal polymer chains is delayed, and the mobility of the polymer chains is enhanced, thereby improving the ionic conductivity without deteriorating the mechanical properties. DETAILED DESCRIPTION
[0042] Hereinafter, for better understanding of the present disclosure, the present disclosure will be described in more detail.
[0043] The terms or words used in the specification and the appended claims should not be construed as limited to the ordinary or dictionary meanings, but should be interpreted with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his own invention in the best manner.
[0044] As used herein, the term "bond," i.e., with respect to the conformation in which a polar compound is "bonded" to a polymer chain (e.g., a chain of a PEO-based copolymer), broadly refers to a conformation in which a gaseous polar compound (which is a polar solvent molecule) remains fixed to a polymer chain by vapor deposition of the polar solvent. In other words, "bond" is not limited to a specific type of physical bond, chemical bond, or the like, but refers to a state in which the polar compound is fixed by various bonds including physical bonds, chemical bonds, or is simply attached and fixed (e.g., by adsorption, etc.), or is contained in a three-dimensional network structure formed by polymer crosslinking and is located near a polymer chain or crosslinked structure and fixed.
[0045] As used herein, the term "three-dimensional network structure" refers to a structure comprising a three-dimensional framework and an internal space formed by the framework, wherein the framework may include polymer chains including cross-links formed by cross-linkable functional groups, for example, cross-links between cross-linkable functional groups and / or cross-links between a cross-linkable functional group and a cross-linking agent. The three-dimensional network structure may also be referred to as a cross-linked structure.
[0046] In the present disclosure, the polar compound (polar solvent) exists in a "gaseous state" or is contained in a composite solid electrolyte, indicating that, unlike the case where the polar solvent or the electrolyte containing the polar solvent is injected in a liquid state, the polar compound is deposited in a vapor state, and the polar compound exists in a state different from the liquid-injected electrolyte just after the composite solid electrolyte is prepared or during the charging and discharging process of the all-solid-state secondary battery containing the composite solid electrolyte. However, depending on the storage or operating conditions of the composite solid electrolyte and / or the secondary battery, the vapor-deposited polar compound may have a partially or temporarily liquefied state. Even in this case, the vapor-deposited polar compound exhibits higher mobility than the polar solvent injected in a liquid state, and exhibits a state different from the liquid polar solvent, which can also be considered to be present or contained in the above-mentioned "gaseous state".
[0047] On the other hand, conventionally, composite solid electrolytes have been prepared to improve the ionic conductivity of solid electrolytes by dispersing ceramic compounds such as oxides within a polymer matrix. However, these composite solid electrolytes suffer from reduced ionic conductivity when the oxide ceramic particles are unevenly distributed within the polymer matrix or when a highly crystalline polymer such as polyethylene oxide is used as the polymer.
[0048] In addition, conventionally, in order to improve the ionic conductivity of the solid electrolyte, the solid electrolyte is immersed in or loaded on a liquid electrolyte or solvent, or the liquid electrolyte or solvent is directly injected into the solid electrolyte in a liquid state. When the liquid electrolyte or solvent is directly added to the solid electrolyte in this way, the ionic conductivity of the solid electrolyte is improved, but this is only based on the high ionic conductivity of the liquid itself to improve the ionic conductivity of the solid electrolyte. The degree of improvement is also insufficient, and a large amount of liquid electrolyte needs to be injected. In other words, since the conduction of lithium ions is achieved by the liquid electrolyte added to the solid electrolyte rather than the inherent physical properties of the solid electrolyte, it is far from improving the physical properties of the solid electrolyte itself. In addition, when the liquid electrolyte or solvent is directly added or injected into the solid electrolyte in liquid form, there is the following problem: due to undesirable side reactions between the polymer and the liquid phase, the structure of the solid electrolyte collapses, such as damage to the polymer chain or breakage of the polymer internal bond, or the ionic conductivity is reduced.
[0049] In addition, when solvents or liquid electrolytes are directly injected into solid electrolytes, the liquid molecules diffuse rapidly within the solid electrolyte, quickly causing relaxation of the polymer chains and promoting surface gelation, which may lead to a decrease in mechanical properties, and problems such as liquid leakage of the liquid electrolyte may not be completely solved.
[0050] Japanese Patent Application Laid-Open No. 1994-124713 discloses a technique for vapor-depositing a solvent onto a general PEO (polyethylene oxide) polymer. However, this technique causes the internal structure of the polymer to collapse, and ionic conductivity cannot be ensured.
[0051] Therefore, the present inventors have applied a method for vapor-depositing a polar compound from a polar solvent onto a composite solid electrolyte containing a ceramic compound and a polymer cross-linked with a PEO (polyethylene oxide)-based copolymer modified with a cross-linkable functional group. A composite solid electrolyte of one embodiment prepared in this manner includes: a polymer containing a PEO (polyethylene oxide)-based copolymer containing a cross-linkable functional group; a ceramic compound; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-links with each other, such that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or can represent a structure bonded to the polymer chain.
[0052] The composite solid electrolyte was confirmed to exhibit improved ionic conductivity when containing trace amounts of gaseous polar compounds derived from polar solvents. This is presumably because the gaseous polar compounds affect the crystallinity and other physical properties of the PEO-based copolymer and increase the mobility of the polymer chains, thereby improving the conductivity of lithium ions contained in the composite solid electrolyte.
[0053] Furthermore, the composite solid electrolyte can exhibit excellent ionic conductivity due to the uniform dispersion of the ceramic compounds within the three-dimensional network structure.
[0054] Therefore, the composite solid electrolyte of one embodiment exhibits improved ionic conductivity in the absence of substantially any liquid polar solvent or electrolyte, and can greatly contribute to the development of all-solid-state batteries having excellent physical properties.
[0055] Next, the composite solid electrolyte according to the embodiment of the present disclosure will be described in detail.
[0056] Composite solid electrolyte
[0057] As described above, a composite solid electrolyte of one embodiment includes: a polymer comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; a ceramic compound; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-linked bonds with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to the polymer chain.
[0058] In a specific example, the gaseous polar compound may be dispersed between polymer chains forming a three-dimensional network structure, or may have a conformation of being adsorbed or bonded to the surface or interior of the polymer chain.
[0059] The composite solid electrolyte is substantially free of liquid solvents or electrolytes and contains trace amounts of polar compounds that are contained or bonded in a gaseous state by vapor deposition, which will be described later. The composite solid electrolyte can be confirmed by the following facts: for example, when the electrolyte layer containing the composite solid electrolyte is separated from the all-solid-state battery and then observed with the naked eye or an electron microscope, no liquid component is observed on the surface of the electrolyte layer. In contrast, when a liquid polar solvent or electrolyte is injected into the composite solid electrolyte, a liquid component or a component exhibiting wettability can be observed on the surface of the electrolyte layer. In addition, as confirmed by the examples described later, a composite solid electrolyte of an embodiment in which a polar compound is vapor-deposited and contained in a gaseous state exhibits a significantly higher ionic conductivity than when a liquid polar solvent or electrolyte is injected. By comparing this ionic conductivity, a composite solid electrolyte in which a polar compound is vapor-deposited and contained in a gaseous state can be confirmed.
[0060] In the composite solid electrolyte of one embodiment, the crosslinkable functional group can be directly bonded to the main chain of the PEO-based copolymer, or can be bonded through an alkylene or oxyalkylene linker. Therefore, the crosslinkable functional group can be bonded through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and can be at least one selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
[0061] In one embodiment of the present disclosure, the crosslinkable functional groups may be composed of two or more. The crosslinkable functional groups may be the same or different from each other, and preferably may be different. When the crosslinkable functional groups are different, multiple repeating units each containing these functional groups may be included. In addition, when multiple crosslinkable functional groups are included, the mobility and ionic conductivity of the polymer chain can be more easily controlled.
[0062] The crosslinkable functional group refers to a functional group capable of forming a crosslink bond between crosslinkable functional groups and / or forming a crosslink bond with each other via a crosslinking agent, and may be bonded to the main chain of the polymer chain in the form of a side chain.
[0063] In a more specific example, the PEO-based copolymer containing a cross-linkable functional group may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:
[0064] [Chemical Formula 1]
[0065]
[0066] [Chemical Formula 2]
[0067]
[0068] [Chemical Formula 3]
[0069]
[0070] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms,
[0071] R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to the polymer chain through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms (provided that the alkylene linker having 0 carbon atoms represents a single bond), and
[0072] l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
[0073] For example, the crosslinkable functional group of R2 can form a polymer in the form of a matrix having a three-dimensional network structure formed by crosslinking. The three-dimensional network structure formed by crosslinking can improve the mechanical properties of the composite solid electrolyte, and a gaseous polar compound can be included or bonded within this three-dimensional network structure to provide a composite solid electrolyte of one embodiment with improved ionic conductivity.
[0074] In addition, it is apparent that the PEO-based copolymer may include two or more repeating units of Chemical Formula 3, wherein R2 is a cross-linkable functional group different from each other, and may also include one or more repeating units of Chemical Formula 2.
[0075] When l, m, and n are each less than 1, it is difficult to form a polymer due to the small molecular weight, and when l, m, and n are each greater than 1000, the solubility during the preparation of the polymer solution decreases due to the increased viscosity, and molding for preparing a composite solid electrolyte may become difficult. In particular, when the number of repetitions of the repeating unit containing a crosslinkable functional group in l, m, and n exceeds 1000, the degree of crosslinking increases excessively, the mobility of the polymer chain may decrease, and the ionic conductivity may decrease.
[0076] As used herein, "hydroxy" refers to an -OH group.
[0077] As used herein, "carboxyl" refers to a -COOH group.
[0078] As used herein, "isocyanate" refers to a -N=C=O group.
[0079] As used herein, "nitro" refers to a -NO2 group.
[0080] As used herein, "cyano" refers to a -CN group.
[0081] As used herein, "amido" refers to -C(=O)NR'R", wherein R' and R" can each independently be hydrogen or C1 to C5 alkyl, or R' and R" together with the nitrogen atom to which they are attached can form a heterocycle having 4 to 8 carbon atoms in the ring structure.
[0082] As used herein, the "amino group" may be selected from the group consisting of a monoalkylamino group, a monoarylamino group, a monoheteroarylamino group, a dialkylamino group, a diarylamino group, a diheteroarylamino group, an alkylarylamino group, an alkylheteroarylamino group, and an arylheteroarylamino group, and the carbon number thereof is not particularly limited, but is preferably 1 to 30. Specific examples of the amino group include a methylamino group, a dimethylamino group, an ethylamino group, a diethylamino group, a phenylamino group, a naphthylamino group, a biphenylamino group, a diphenylamino group, an anthrylamino group, a 9-methyl-anthrylamino group, a diphenylamino group, a phenylnaphthylamino group, a ditolylamino group, a phenyltolylamino group, a triphenylamino group, a biphenylnaphthylamino group, a phenylbiphenylamino group, a biphenylfluorenylamino group, a phenyltriphenyleneamino group, and a biphenyltriphenyleneamino group, but are not limited thereto. In addition, the "amino group" refers to -NH2.
[0083] As used herein, "allyl" refers to a -CH2-CH=CH2 group.
[0084] The weight average molecular weight (Mw) of the copolymer containing chemical formula 1 to 3 can be 100,000g / mol to 2,000,000g / mol, specifically, it can be more than 100,000g / mol, more than 200,000g / mol or more than 300,000g / mol and less than 1,600,000g / mol, less than 1,800,000g / mol or less than 2,000,000g / mol. If the weight average molecular weight (Mw) of the copolymer is less than 100,000g / mol, it may not be possible to meet the mechanical properties of the composite solid electrolyte to be prepared. If the weight average molecular weight (Mw) of the copolymer is greater than 2,000,000g / mol, the solubility during the preparation of the polymer solution decreases due to increased viscosity, and the molding for preparing the composite solid electrolyte may become difficult. In addition, due to the increase in the crystallinity inside the composite solid electrolyte and the reduction in chain mobility, the ionic conductivity of the composite solid electrolyte may decrease.
[0085] In particular, when the number of repetitions of the repeating unit of Formula 3 containing a crosslinkable functional group in l, m, and n is greater than 1000, the crosslinking degree excessively increases and the mobility of the polymer chain decreases, thereby reducing the ionic conductivity of the composite solid electrolyte.
[0086] Furthermore, the copolymer may be a random copolymer or a block copolymer.
[0087] In a specific embodiment of the present disclosure, the polar compound may be contained in or bonded to the surface or interior of the polymer chain in a gaseous state. Specifically, the gaseous polar compound may diffuse or disperse between the polymer chains that form a three-dimensional network structure through cross-linking, or may be adsorbed or bonded to the surface or interior of the polymer chain.
[0088] Polar compounds are gas molecules of the polar solvent used in the vapor deposition process. These compounds may be adsorbed onto the polymer during vapor deposition, then diffuse into and bond to the polymer chains, or dispersed or diffused within the spaces between the polymer chains. The polar compound bonds to the polymer chains or disperses within the spaces between the polymer chains, thereby improving the ionic conductivity of the resulting composite solid electrolyte.
[0089] Specifically, polar compounds bonded to or contained between polymer chains can act as plasticizers and plasticize the polymer. The plasticized polymer interior may have increased amorphous regions, which can improve the mobility of the polymer chains. As the mobility of the polymer chains increases, the ion hopping effect inside the polymer increases, which can improve the ionic conductivity of the composite solid electrolyte.
[0090] Furthermore, polar compounds can serve as intermediates for smooth ion transport via ion hopping. Because the affinity between lithium ions and polar compounds is stronger than the affinity between lithium ions and the ether oxygen of PEO-based copolymers, lithium ion transport within polymers adsorbed with polar compounds can be faster and easier. Specifically, as the polar compound flows into the polymer, the cationic solvation effect of lithium ions increases, improving ion mobility and thereby enhancing the ionic conductivity of the composite solid electrolyte.
[0091] In addition, the polar compound may include at least one selected from the group consisting of carbonate-based compounds and sulfonyl-based compounds.
[0092] Specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane, or a combination thereof.
[0093] Based on the gross weight of composite solid electrolyte, the content of polar compound can include more than 0.1 wt % and less than 10 wt %.For example, the content of polar compound can be more than 0.1 wt %, more than 1 wt % and less than 2 wt % or less than 5 wt %, less than 6 wt %, less than 7 wt %, less than 8 wt % or less than 9 wt % or less than 10 wt %.When the content of polar compound is less than 0.1 wt %, it is difficult to cause the change of chain conformation inside polymer, and therefore, the ionic conductivity of composite solid electrolyte does not improve.When the content of polar compound is more than 10 wt %, composite solid electrolyte has larger liquid content and has the performance of semi-solid battery.In addition, due to the gelation of polymer, the mechanical strength of composite solid electrolyte may reduce.
[0094] In one embodiment of the present disclosure, the composite solid electrolyte may include crosslinks between crosslinkable functional groups. In addition, the composite solid electrolyte may further include a crosslinking agent to form crosslinks between the crosslinking agent and the crosslinkable functional groups. For example, at least a portion of the crosslinkable functional groups may be crosslinked with each other via the crosslinking agent, thereby forming the above-mentioned three-dimensional network structure.
[0095] The cross-linking bond may be a urethane cross-linking bond, an ester cross-linking bond, a hydrogen bond, a bond formed by radical polymerization of a vinyl group at the end of an allyl group (-CH2-CH=CH2), etc., but is not limited to these examples.
[0096] Furthermore, when a crosslinking agent is added during the preparation of the composite solid electrolyte, crosslinking bonds can be formed between the crosslinking agent and the crosslinkable functional groups. The crosslinking bonds can be hydrogen bonds, bonds formed by Lewis acid-base interactions, ionic bonds, coordination bonds, or bonds formed by free radical polymerization.
[0097] The cross-linking agent is not particularly limited as long as it is a multifunctional cross-linking agent that can form a cross-linked bond with a cross-linkable functional group. For example, the cross-linking agent can be selected from trimethylolpropane trimethacrylate, poly (ethylene glycol) diacrylate, poly (ethylene glycol) dimethacrylate, ethylene glycol dimethacrylate (hereinafter referred to as "EGDMA"), 1,3-diisopropenylbenzene (DIP), 1,4-diacryloylpiperazine, 2- (diethylamino) ethyl methacrylate, 2,6-bisacryloylaminopyridine, 3- (acryloyloxy) -2-hydroxypropyl methacrylate, 3,5-bis (acryloylamino) benzoic acid, 3-aminopropyl triethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-methacryloyloxypropyl trimethoxysilane, bis- (1- One or more polyfunctional crosslinking agents selected from the group consisting of (tert-butylperoxy)-1-methylethyl)-benzene, dicumyl peroxide, dimethacrylate, divinylbenzene, maleated rosin glycol acrylate, glycidyl methacrylate, hydroxyquinoline, i-phenyldiethoxysilane, maleated rosin glycol acrylate, methylenebisacrylamide, N,N'-1,4-phenylenedipropyleneamine, N,O-bisacryloyl-phenylalaninol, N,O-bismethacryloylethanolamine, pentaerythritol triacrylate, phenyltrimethoxysilane, tetramethoxysilane, tetramethylene compounds, tetraethoxysilane and triallyl isocyanurate, for example, a polyvalent compound having two or more functional groups.
[0098] In addition, the content of the crosslinking agent may be 1 to 30 parts by weight based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group. If the content of the crosslinking agent is less than 1 part by weight, sufficient crosslinking with the crosslinkable functional group may not be achieved, and if the content of the crosslinking agent is greater than 30 parts by weight, excessive crosslinking may occur and the mobility of the polymer chain may be reduced, thereby resulting in reduced ionic conductivity.
[0099] In one embodiment of the present disclosure, the composite solid electrolyte may further include a lithium salt. The lithium salt is contained in the internal space between the polymer chains in a dissociated ionic state, thereby improving the ionic conductivity of the composite solid electrolyte. At least a portion of the cations and / or anions dissociated from the lithium salt remain bound to the polymer chains and can exhibit mobility during charge / discharge of the battery.
[0100] The lithium salt may include a salt selected from the group consisting of (CF3SO2)2NLi (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, at least one of the group consisting of LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, lithium chloroborane, lower aliphatic carboxylic acid lithium and lithium tetraphenylborate.
[0101] In addition, based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the content of the lithium salt may be 25 to 45 parts by weight. Specifically, its content may be 25 parts by weight or more, 30 parts by weight or more, or 35 parts by weight or more, or 40 parts by weight or less, or 45 parts by weight or less. If the content of the lithium salt is less than 25 parts by weight, the ionic conductivity of the composite solid electrolyte may be reduced, and if the content of the lithium salt exceeds 45 parts by weight, the mechanical strength may be reduced.
[0102] The composite solid electrolyte may include a ceramic compound having lithium ion transport capability to improve lithium ion conductivity, preferably containing lithium atoms but not storing lithium, and having the function of transporting lithium ions and improving the ionic conductivity of the composite solid electrolyte.
[0103] Furthermore, the ceramic compound can be uniformly dispersed between crosslinked polymer chains, for example within a three-dimensional network structure. The ceramic compound is incorporated during the crosslinking process and can be uniformly dispersed between the crosslinked polymer chains without agglomerating. This uniform dispersion of the ceramic compound can improve the mechanical strength and ionic conductivity of the composite solid electrolyte.
[0104] Furthermore, the ceramic compound may be in the form of particles. Due to the morphological characteristics of the particles, they can be contained in the composite solid electrolyte in a more uniformly dispersed state. The particles of the ceramic compound may be spherical, and their diameter may be 100 nm to 1000 nm. If the diameter is less than 100 nm, the amorphization effect due to the decrease in polymer crystallinity may be small, and if the diameter is greater than 1000 nm, the dispersibility may be reduced due to increased aggregation between the particles, which may make uniform dispersion difficult.
[0105] The ceramic compound may be an oxide or phosphate compound, for example, an oxide solid electrolyte in the form of lithium metal oxide or lithium metal phosphate. More specifically, the ceramic compound may be selected from garnet-type lithium lanthanum zirconium oxide (LLZO, Li7La3Zr2O 12 ) compounds, perovskite-type lithium lanthanum titanium oxide (LLTO, Li3xLa 2 / 3-x TiO3) compounds, phosphate NASICON type lithium aluminum titanium phosphate (LATP, Li 1+x Alx Ti 2-x (PO4)3) compounds, lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 At least one of the group consisting of (PO4)3) compounds, lithium silicon titanium phosphate (LSTP, LiSiO2TiO2(PO4)3) compounds and lithium lanthanum zirconium titanium oxide (LLZTO) compounds. More preferably, at least one oxide-based solid electrolyte selected from the group consisting of lithium lanthanum zirconium oxide (LLZO), lithium silicon titanium phosphate (LSTP), lithium lanthanum titanium oxide (LLTO), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP) and lithium lanthanum zirconium titanium oxide (LLZTO) can be used.
[0106] Oxide-based or phosphate-based solid electrolytes usually have a high -4 to 10 -3 S / cm, and has the advantages of being stable in high voltage regions, stable in air, and easy to synthesize and handle.
[0107] Therefore, the above-mentioned composite solid electrolyte may further include a composite solid electrolyte mixed with a ceramic compound to compensate for the shortcomings of the polymer-based solid electrolyte.
[0108] Furthermore, ceramic compounds are not prone to burning or igniting even at temperatures exceeding 400°C, resulting in high-temperature stability. Therefore, when a composite solid electrolyte contains a ceramic compound, it not only improves the mechanical strength of the composite solid electrolyte but also its high-temperature stability and ionic conductivity.
[0109] The ceramic compound may be included in an amount of 10 to 100 parts by weight, or 10 to 60 parts by weight, based on 100 parts by weight of the PEO-based copolymer containing a cross-linkable functional group.
[0110] If the content of the ceramic compound is too small, the effect of the ceramic compound on reducing the crystallinity of the polymer and making it amorphous is reduced, so the effect of improving the ionic conductivity of the composite solid electrolyte is not significant, and the mechanical properties may not reach the expected level due to the formation of the composite material.
[0111] If the content of the ceramic compound is too high, the ceramic compound cannot be uniformly dispersed in the polymer, and the ceramic compound particles may agglomerate and aggregate with each other, thereby preparing a polymer solid electrolyte with reduced ionic conductivity.
[0112] Preparation method of composite solid electrolyte
[0113] In another disclosed embodiment, the preparation method of the above-mentioned composite solid electrolyte may include the following steps: (S1) mixing a PEO (polyethylene oxide)-type copolymer containing a cross-linkable functional group with a ceramic compound, and then subjecting the PEO-type copolymer contained in the mixture to a cross-linking reaction; and (S2) vapor-depositing a polar solvent on the mixture containing the polymer cross-linked in step (S1).
[0114] The description of the PEO-based copolymer containing a cross-linkable functional group is the same as above.
[0115] Each step is described in more detail below.
[0116] In step (S1), a PEO (polyethylene oxide) copolymer containing a crosslinkable functional group is mixed with a ceramic compound, and then the PEO copolymer contained in the mixture is crosslinked to prepare a polymer forming the above-mentioned three-dimensional network structure.
[0117] The cross-linking reaction in step (S1) may be performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.
[0118] Furthermore, in order to form a composite solid electrolyte, a lithium salt may also be added in step (S1).
[0119] In addition, the ceramic compound may be the same as the ceramic compound used in the above-mentioned composite solid electrolyte, and its content may also be used similarly.
[0120] The cross-linking reaction can be performed by applying a solution containing a PEO-based copolymer, a ceramic compound, etc. on a substrate to form a coating film, and then drying the coating film.
[0121] Specifically, the mixed solution can be prepared by mixing the PEO-based copolymer and the ceramic compound in a solvent, and further, the solution can be prepared by mixing a cross-linking agent, an initiator and / or a lithium salt. In addition, a solution containing the PEO-based copolymer, a cross-linking agent, an initiator and / or a lithium salt can be first prepared, and then the ceramic compound can be added thereto to prepare a mixed solution or suspension.
[0122] The solvent is not particularly limited as long as it is a solvent that can be mixed with the PEO copolymer, cross-linking agent, initiator and / or lithium salt and can be easily removed by a drying process. For example, the solvent can be acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP) or N, N-dimethylformamide (DMF) and the like. This solvent is a solvent used as a reaction medium for forming a cross-linked bond, which is different from the polar solvent contained in the liquid electrolyte and is completely removed by drying and the like after cross-linking.
[0123] In view of the degree that the forming process of preparing composite solid electrolyte can be carried out smoothly, the concentration of mixed solution can be appropriately regulated. Specifically, the concentration of polymer solution can refer to the concentration (weight %) of polymer in polymer solution. The concentration of polymer can be the concentration of PEO type copolymer. For example, the concentration of polymer solution can be 5 weight % to 20 weight %, specifically, can be more than 5 weight %, more than 7 weight % or more than 9 weight % and less than 13 weight %, less than 17 weight % or less than 20 weight %. If the concentration of polymer solution is less than 5 weight %, then concentration may be too dilute, and the mechanical strength of composite solid electrolyte may reduce, or when being coated on substrate, it may flow downward. If the concentration of polymer solution is greater than 20 weight %, then it is difficult to dissolve lithium salt in polymer solution with desired concentration, viscosity can be high, and solubility can be low, which makes it difficult to apply lithium salt in the form of uniform film.
[0124] The substrate is not particularly limited as long as it can be used as the support of the coating. For example, the substrate can be SUS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film or polyimide film.
[0125] In addition, the coating method is not particularly limited as long as it can form a coating film by applying the polymer solution to the substrate. For example, the coating method can be rod coating, roller coating, spin coating, slit coating, die coating, blade coating, comma coating, slit die coating, lip coating, spray coating or solution casting.
[0126] The coating film formed on the substrate by the coating method can be formed into a membrane-type polymer in which the residual solvent is completely removed by the drying process. Drying can be divided into a primary drying process and a secondary drying process to prevent the polymer from shrinking due to the rapid evaporation of the solvent. The primary drying process can remove part of the solvent by room temperature drying, and the secondary drying process can completely remove the solvent by vacuum high temperature drying. High temperature drying can be carried out at a temperature of 80°C to 130°C. If the high temperature drying temperature is less than 80°C, the residual solvent cannot be completely removed, and if the high temperature drying temperature is greater than 130°C, the polymer will shrink, which makes it difficult to form a uniform electrolyte membrane.
[0127] In addition, the crosslinking agent can form a bond with the crosslinkable functional group. The type of crosslinking agent, the content of the crosslinking agent, and the type of bonding with the crosslinkable functional group are the same as described above.
[0128] In addition, the initiator can induce a free radical polymerization reaction between the crosslinkable functional groups to form a crosslinking bond between the crosslinkable functional groups. The functional group capable of free radical polymerization can be a functional group containing a terminal vinyl group, such as an allyl group.
[0129] The initiator is not particularly limited as long as it is an initiator that can induce a free radical polymerization reaction between crosslinkable functional groups. For example, the initiator may include at least one selected from the group consisting of benzoyl peroxide, azobisisobutyronitrile, lauroyl peroxide, cumene hydroperoxide, diisopropylphenyl hydroperoxide, tert-butyl hydroperoxide, p-methane hydroperoxide, and 2,2'-azobis(2-methylpropionitrile).
[0130] Based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the initiator can be used in an amount of 0.5 to 2 parts by weight. When the initiator is used within the above range, it can induce a free radical polymerization reaction between the crosslinkable functional groups and effectively form a crosslink bond.
[0131] Otherwise, the content and type of the lithium salt are the same as above.
[0132] In step (S2), a polar solvent may be vapor-deposited on the mixture containing the cross-linked polymer prepared in step (S1) to prepare the composite solid electrolyte of one embodiment described above. In this case, the gas molecules of the polar solvent may be the polar compound included in one embodiment.
[0133] Vapor deposition can be performed by contacting a polymer with the vapor of a polar solvent, either at room temperature or generated by heating, and allowing the vapor to penetrate the polymer. In this way, gaseous polar compounds are uniformly diffused on the surface and / or within the polymer by vapor deposition at room temperature or by heating. The polar compound gas molecules may be bonded to the polymer chain or contained within the internal space of the polymer chain in a uniformly dispersed or diffused form.
[0134] If the polar solvent is kept at room temperature during vapor deposition, a trace amount of the low-boiling-point polar solvent can slowly vaporize at room temperature and penetrate into the interior of the polymer, effectively inducing conformational changes in the cross-linked polymer chains within the polymer.
[0135] In addition, when the polar solvent is heated during vapor deposition, the vapor deposition rate can be increased. At this time, the heating temperature is not particularly limited, as long as it is a temperature at which the polar solvent can undergo a phase change into a vapor, for example, it can be 30°C to 80°C. General PEO melts at 60°C, but when a PEO-based copolymer modified with a cross-linkable functional group forms a cross-linked structure, its heat resistance is improved and can withstand up to 80°C, thereby further increasing the vapor deposition rate. In addition, the heating method is not limited, as long as it is a method that can supply energy to generate steam. For example, a direct heating method using a burner or a furnace, or an indirect heating method using a heater or a steam pipe, etc. can be used, but the method is not limited to these examples.
[0136] If the temperature is too high during heating, the solvent may boil at a temperature higher than the boiling point of the polar solvent, causing structural changes in the solvent or causing deformation of the polymer. Furthermore, it is difficult to control the evaporation rate of the polar solvent during vapor deposition. For vapor deposition using a trace amount of a polar solvent, it is desirable to perform vapor deposition at a heating temperature within the appropriate range specified above.
[0137] All-solid-state batteries
[0138] Another embodiment of the present disclosure also relates to an all-solid-state battery comprising the above-mentioned composite solid electrolyte, wherein the all-solid-state battery comprises a negative electrode, a positive electrode, and a composite solid electrolyte between the negative electrode and the positive electrode, and the composite solid electrolyte is based on one of the above-mentioned embodiments.
[0139] Specifically, the composite solid electrolyte includes a polymer cross-linked with a PEO (polyethylene oxide)-type copolymer containing a cross-linkable functional group and a gaseous polar compound, which contains or bonds the gaseous polar compound to make the ceramic compound uniformly dispersed and improve the ionic conductivity, which can be suitable as an electrolyte for an all-solid-state battery.
[0140] On the other hand, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, wherein the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0141] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0142] In addition, the positive electrode active material is not particularly limited as long as it is a material that can reversibly absorb and desorb lithium ions, and examples thereof may be layered compounds such as lithium cobalt oxide, lithium nickel oxide, Li[Ni x Co y Mn z M v]O2 (wherein M is any one selected from the group consisting of Al, Ga and In, or two or more thereof; and 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1 and x+y+z+v=1), Li(Li a M b-a-b' M' b' )O 2-c A c (wherein 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2 and 0≤c≤0.2; M comprises Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is at least one selected from the group consisting of Al, Mg and B; A is at least one selected from the group consisting of P, F, S and N), or a compound substituted with at least one transition metal; lithium manganese oxide, such as a compound of the formula Li 1+y Mn 2-y O4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; chemical formula LiNi 1-y Ni-type lithium nickel oxide represented by MyO2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li is replaced by alkaline earth metal ions; disulfides; and composite oxides formed by Fe2(MoO4)3, but are not limited thereto.
[0143] In addition, the content of the positive electrode active material may be 40 to 80 weight % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 weight % or more or 50 weight % or more, and 70 weight % or less or 80 weight % or less. If the content of the positive electrode active material is less than 40 weight %, the connectivity and electrical properties between the positive electrode active materials may be insufficient, and if the content of the positive electrode active material is greater than 80 weight %, the mass transfer resistance may increase.
[0144] The binder is a component that assists bonding between the positive electrode active material and the conductive material and bonding with the current collector. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride)-hexafluoropropylene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0145] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 1% to 30% by weight. Specifically, the content of the binder may be 1% by weight or more or 3% by weight or more, and 15% by weight or less or 30% by weight or less. If the content of the binder is less than 1% by weight, the adhesion between the positive electrode active material and the positive electrode current collector may be reduced, and if the content of the binder is greater than 30% by weight, the adhesion is improved, but the content of the positive electrode active material is correspondingly reduced, which may reduce the battery capacity.
[0146] In addition, the conductive material is not particularly limited as long as it does not cause side reactions in the internal environment of the all-solid-state battery and does not cause chemical changes in the battery but has excellent conductivity. The conductive material can generally be graphite or conductive carbon, and can be, for example, but not limited to, one selected from the group consisting of: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black (thermal black), channel black, furnace black, lamp black and thermal black (summer black); carbon-based materials having a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; and mixtures of two or more thereof.
[0147] Based on the total weight of the positive electrode active material layer, the content of the conductive material may generally be 0.5 wt % to 30 wt %. Specifically, the content of the conductive material may be more than 0.5 wt % or more than 1 wt %, and less than 20 wt % or less than 30 wt %. If the content of the conductive material is too low, i.e., less than 0.5 wt %, it is difficult to obtain the effect of improving the conductivity, or the electrochemical characteristics of the battery may deteriorate. If the content of the conductive material is too high, i.e., greater than 30 wt %, the amount of the positive electrode active material is relatively small, so the capacity and energy density may be reduced. There is no particular limitation on the method for introducing the conductive material into the positive electrode, and conventional methods known in the prior art may be used, such as coating on the positive electrode active material.
[0148] In addition, the positive electrode current collector supports the positive electrode active material layer and plays a role in transferring electrons between the external wire and the positive electrode active material layer.
[0149] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the all-solid-state battery and has high conductivity. For example, the positive electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, palladium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy.
[0150] In order to improve the bonding strength with the positive electrode active material layer, the positive electrode current collector may have a fine protrusion and depression structure on its surface or may adopt a three-dimensional porous structure. Thus, the positive electrode current collector can be used in any of a variety of forms, including films, sheets, foils, grids, nets, porous bodies, foams, and non-woven fabric structures.
[0151] The positive electrode as described above can be prepared according to a conventional method. Specifically, the positive electrode can be prepared by the following process: a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a conductive material and a binder in an organic solvent is coated on a positive electrode current collector and dried, and the current collector is optionally compression-molded to increase the electrode density. At this time, as an organic solvent, it is preferred to use a solvent that can uniformly disperse the positive electrode active material, the binder and the conductive material and easily evaporate. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP) and the like can be mentioned.
[0152] On the other hand, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0153] The negative electrode active material may include a material capable of reversibly inserting and deinserting lithium (Li + ) material, a material that can react with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.
[0154] Able to reversibly insert and deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0155] Preferably, the negative electrode active material may be lithium metal, specifically, in the form of a lithium metal film or lithium metal powder.
[0156] The content of the negative electrode active material may be 40 to 80% by weight based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40% by weight or more or 50% by weight or more and 70% by weight or less or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the electrical characteristics may be insufficient, and if the content of the negative electrode active material is greater than 80% by weight, the mass transfer resistance may increase.
[0157] In addition, the binder is the same as described above in the positive electrode active material layer.
[0158] In addition, the conductive material is the same as described above in the positive electrode active material layer.
[0159] Furthermore, the negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has conductivity. For example, the negative electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, or silver, or aluminum-cadmium alloy. In addition, similar to the positive electrode current collector, the negative electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric structures having fine protrusions and depressions formed on their surfaces.
[0160] The preparation method of the negative electrode is not particularly limited and can be prepared by forming a negative electrode active material layer on the negative electrode current collector using a layer or film formation method commonly used in the art. For example, methods such as compression, coating, and deposition can be used. In addition, the negative electrode of the present disclosure also includes the case where the battery is assembled in a state where there is no lithium film on the negative electrode current collector and then a metallic lithium film is formed on the metal plate during initial charging.
[0161] According to yet another embodiment, provided are a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0162] Here, specific examples of the device may include, but are not limited to: power tools driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs) or plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; or power storage systems, etc.
[0163] Hereinafter, preferred embodiments will be given so that the present disclosure can be easily understood. However, the following embodiments are for illustrative purposes only, and the scope of the present disclosure is not limited thereto.
[0164] Example
[0165] Example 1: Preparation of composite solid electrolyte
[0166] Step 1) Preparation of polymer containing copolymer
[0167] A polyethylene oxide (PEO) copolymer of the following chemical formula 1a was prepared:
[0168] [Chemical Formula 1a]
[0169]
[0170] Wherein, in Chemical Formula 1a, R1 is -CH2-O-(CH2-CH2-O) k -CH3, R2 is -CH2-O-CH2-CH=CH2, k is 2, the ratio of l:m:n is 85:13:2, and the weight average molecular weight (Mw) of the copolymer is about 2,000,000 g / mol.
[0171] The copolymer of Chemical Formula 1a has allyl groups bonded through oxymethylene linkers as crosslinkable functional groups.
[0172] A polyethylene oxide copolymer was mixed with acetonitrile as a solvent, trimethylolpropane trimethacrylate as a crosslinker, benzoyl peroxide as an initiator, LiTFSI as a lithium salt, and LSTP as a ceramic compound to prepare a mixed solution of the polymer and the ceramic compound, which was then stirred using a magnetic bar for 24 hours. The mixed solution of the polyethylene oxide copolymer and the ceramic compound consisted of the following materials: 20 parts by weight of trimethylolpropane trimethacrylate as a crosslinker, 1 part by weight of benzoyl peroxide as an initiator, 36 parts by weight of LiTFSI as a lithium salt, and 40 parts by weight of LSTP, based on 100 parts by weight of the polyethylene oxide copolymer. The acetonitrile solvent was used so that the concentration of the polyethylene oxide copolymer as a polymer in the mixed solution was 11.1% by weight, and the concentration of the polymer, namely the polyethylene oxide copolymer and the ceramic compound, was 14.9% by weight.
[0173] The prepared mixed solution was solution-cast on the lower substrate of the coin cell, and then dried at room temperature for 12 hours and then dried at 100°C for 3 hours to prepare an electrolyte membrane with a thickness of 200 μm.
[0174] Step 2) Preparation of composite solid electrolyte
[0175] The polymer was attached to the upper plate of the chamber, and the lower part of the chamber was filled with ethyl methyl carbonate (EMC) solvent. The solvent was then naturally evaporated at room temperature for 72 hours to allow the EMC vapor to flow into the polymer attached to the upper part of the chamber. In this way, a composite solid electrolyte was prepared.
[0176] Comparative Example:
[0177] Comparative Example 1: A composite solid electrolyte containing only modified PEO + ceramic compound (excluding solvent).
[0178] A composite solid electrolyte was prepared in the same manner as in Example 1, except that step 2) of Example 1, i.e., vapor deposition of the EMC solvent, was not performed.
[0179] Comparative Example 2: Composite solid electrolyte containing modified PEO + ceramic compound + a large amount of solvent
[0180] A composite solid electrolyte was prepared in the same manner as in Example 1, except that a liquid solvent was directly injected into the composite solid electrolyte prepared in step 1) of Example 1 without performing vapor deposition of an EMC solvent (12 wt %). The EMC solvent was directly injected such that the content of the EMC solvent was 12 wt % based on the total weight of the prepared composite solid electrolyte.
[0181] Comparative Example 3: Unmodified PEO + Ceramic Compound + Composite Solid Electrolyte Deposited with Polar Solvent
[0182] A composite solid electrolyte was prepared in the same manner as in Example 1, except that a polyethylene oxide (PEO) homopolymer (weight average molecular weight: about 4,000,000 g / mol) not substituted with a crosslinkable functional group was used, and no crosslinking agent or initiator was added.
[0183] Comparative Example 4: Modified PEO + polymer solid electrolyte deposited with polar solvent
[0184] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that no ceramic compound was added.
[0185] Experimental example
[0186] Experimental Example 1: Measuring the content of polar compounds
[0187] The content of the polar compound can be measured by using a balance and monitoring the weight of the liquid phase evaporated over time when the solid electrolyte sample is heated. For example, it can be measured by monitoring the weight of the liquid phase evaporated over time when the sample is heated at a temperature of 55 to 70°C or 60°C using a heated electronic balance (AND MS-70). When the amount of polar compound evaporated over time reaches saturation, the saturated amount at this time is considered to be the total amount of polar compound contained in the solid electrolyte. In the embodiments and comparative examples, the polar compound can be ethyl methyl carbonate (EMC).
[0188] Experimental Example 2: Measuring the ionic conductivity of a composite solid electrolyte
[0189] In order to measure the ionic conductivity of the composite solid electrolytes prepared in Examples and Comparative Examples, a 1.7671 cm 2 A composite solid electrolyte was formed on the lower substrate of a coin cell, and then SUS was used as a blocking electrode to manufacture a coin cell for ionic conductivity measurement.
[0190] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25°C with an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and the ionic conductivity of the composite solid electrolyte was calculated using the following equation 1.
[0191] [Equation 1]
[0192]
[0193] Wherein, in Equation 1, σi is the ionic conductivity of the composite solid electrolyte (S / cm), R is the resistance of the composite solid electrolyte measured by electrochemical impedance spectroscopy (Ω), L is the thickness of the composite solid electrolyte (μm), and A refers to the area of the composite solid electrolyte (cm 2 The composite solid electrolyte sample used had L = 200 μm, A = 1.7671 cm 2 .
[0194] Table 1 below shows the content of EMC vapor-deposited (or contained) in the composite (or polymer) solid electrolyte and the measurement results of ionic conductivity.
[0195] [Table 1]
[0196]
[0197] It can be confirmed that the ionic conductivity of the modified PEO-based solid electrolyte (Comparative Example 1) and the solid electrolyte directly injected with liquid EMC (Comparative Example 2) is 10 -4 S / cm, while the ionic conductivity of the composite solid electrolyte (Example 1) containing a gaseous polar solvent (EMC) and dispersed with a ceramic compound in the modified PEO by a vapor deposition process was increased to 10 -3 This is believed to be because, due to the vapor deposition of the polar solvent (EMC), the gaseous polar solvent compound diffuses into the cross-linked three-dimensional network structure of PEO, or is adsorbed or bonded to the polymer chain, thereby improving the mobility of lithium ions.
[0198] In addition, for general PEO-based solid electrolytes that were not cross-linked or modified as in Comparative Example 3, the effect of improving ionic conductivity due to vapor deposition of polar solvents was not observed. In particular, the internal structure of the polymer collapsed due to the lack of a cross-linked structure, and an internal short-circuit state in which ionic conductivity could not be measured was confirmed.
[0199] Furthermore, as in Comparative Example 4, the ionic conductivity of the solid electrolyte containing a polar solvent (EMC) but no ceramic compound by the vapor deposition process of modified PEO was 10 -4 S / cm. Unlike Example 1, the ionic conductivity is slightly lower due to the absence of ceramic compounds.
[0200] Experimental Example 3: Measuring the Low-Temperature Ionic Conductivity of Composite Solid Electrolytes
[0201] For the composite solid electrolytes of Example 1 and Comparative Example 1, ionic conductivity was measured at a temperature of -30°C to 0°C and is shown in the following Table 2. However, except for the above-mentioned measurement temperature, the method and conditions for measuring ionic conductivity were performed in the same manner as in Experimental Example 2.
[0202] [Table 2]
[0203]
[0204] With reference to Table 2, it was confirmed that the composite solid electrolyte of Example 1 exhibited very excellent ion conductivity compared with Comparative Example 1 even at low temperatures.
Claims
1. A composite solid electrolyte comprising: A polymer comprising a PEO (polyethylene oxide) type copolymer containing a crosslinkable functional group; Ceramic compounds; as well as Polar compounds, wherein at least a portion of the cross-linkable functional groups form cross-links with each other, so that the polymer forms a three-dimensional network structure, and The polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to a polymer chain.
2. The composite solid electrolyte according to claim 1, wherein The polar compound in a gaseous state is dispersed between polymer chains forming the three-dimensional network structure, or is adsorbed or bonded to the surface or inside of the polymer chains.
3. The composite solid electrolyte according to claim 1, wherein The composite solid electrolyte also includes a cross-linking agent.
4. The composite solid electrolyte according to claim 3, wherein At least a portion of the cross-linkable functional groups form cross-linked bonds with each other through the cross-linking agent.
5. The composite solid electrolyte according to claim 1, wherein The PEO-based copolymer contains two or more cross-linkable functional groups.
6. The composite solid electrolyte according to claim 1, wherein The crosslinkable functional group is bonded to the PEO-based copolymer through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and The cross-linkable functional group is selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.
7. The composite solid electrolyte according to claim 1, wherein The composite solid electrolyte also includes a lithium salt.
8. The composite solid electrolyte according to claim 1, wherein The PEO (polyethylene oxide) copolymer is a copolymer containing repeating units of the following chemical formulas 1 to 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.
9. The composite solid electrolyte according to claim 8, wherein: The PEO-based copolymer includes two or more repeating units of Chemical Formula 3, wherein R2 are cross-linkable functional groups different from each other.
10. The composite solid electrolyte according to claim 1, wherein The content of the polar compound is 0.1 wt % or more and less than 10 wt % based on the total weight of the composite solid electrolyte.
11. The composite solid electrolyte according to claim 1, wherein The polar compound includes at least one selected from the group consisting of carbonate compounds and sulfonyl compounds.
12. The composite solid electrolyte according to claim 1, wherein The polar compound includes at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.
13. The composite solid electrolyte according to claim 1, wherein The ceramic compound includes an oxide-based solid electrolyte selected from lithium metal oxides or lithium metal phosphorus oxides.
14. The composite solid electrolyte according to claim 1, wherein The ceramic compound includes at least one oxide-based solid electrolyte selected from the group consisting of a lithium lanthanum zirconium oxide (LLZO) compound, a lithium silicon titanium phosphate (LSTP) compound, a lithium lanthanum titanium oxide (LLTO) compound, a lithium aluminum titanium phosphate (LATP) compound, a lithium aluminum germanium phosphate (LAGP) compound, and a lithium lanthanum zirconium titanium oxide (LLZTO) compound.
15. A method for preparing the composite solid electrolyte according to claim 1, the method comprising the following steps: (S1) mixing a PEO (polyethylene oxide) copolymer containing a crosslinkable functional group with a ceramic compound, and then subjecting the PEO copolymer contained in the mixture to a crosslinking reaction; as well as (S2) vapor-depositing a polar solvent onto the mixture containing the polymer cross-linked in step (S1).
16. The method for preparing a composite solid electrolyte according to claim 15, wherein: The step (S1) is performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.
17. The method for preparing a composite solid electrolyte according to claim 15, wherein: The polar solvent includes at least one selected from the group consisting of carbonate-based solvents and sulfonyl-based solvents.
18. The method for preparing a composite solid electrolyte according to claim 15, wherein: In the step (S2), the vapor of the polar solvent is deposited on the polymer so that the content of the polar solvent is 0.1 wt% or more and less than 10 wt% based on the total weight of the composite solid electrolyte.
19. An all-solid-state battery comprising an electrolyte layer, wherein the electrolyte layer comprises the composite solid electrolyte according to any one of claims 1 to 14.
Citation Information
Patent Citations
Manufacture of polymeric sold electrolyte
JP1994124713A
The structure of the opening and closing control unit for discharging seeds and fertilizers of the multipurpose manual seeding machine
KR1020220132765A
Composition for sealing and sealing sheet
KR1020230136066A